Synthesis and evaluation of the optical properties of novel thermally stable phenanthrolines bearing a arylthienyl-imidazo conjugation pathway - Batista, Rosa Maria Ferreira (2009)
Six new hyperpolarizable chromophores 3-4 based on functionalized arylthiophene donors and an imidazo-phenanthroline acceptor moiety have been designed and synthesized for the first time in good to excellent yields by condensation of 5,6-phenantroline-dione 2 with formyl-arylthiophene derivatives 1 in the presence of ammonium acetate in glacial acetic acid. The thermal stability, solvatochromic and nonlinear optical properties of these compounds were evaluated.